Requirements for Universally Accessible Upper-Body Exercise Equipment: The Case of People with Spinal Cord Injuries in Korea - Kwang-Ok An; Myo-Jung Choi; Sung-Shin Kim; Bo-Ra Kang; Young-Hyeon Bae; Hyosun Kweon (Occupational Therapy International)
Background. People with disabilities face considerable obstacles when exercising, which precludes them from the social and health benefits of physical activity. Especially for individuals with paraplegia with spinal cord injuries, it is necessary to maintain continuous participation in physical activity even after discharge, as it helps to maintain mobility and daily living activities through upper body strength. However, the participation rate of people with disabilities in physical activity in Korea is still low, mainly due to the lack of exercise equipment and facilities. Objectives. The aim of this study is to identify aspects that can be improved for better accessibility to exercise equipment for individuals with paraplegia with spinal cord injuries and to reach a consensus on possible guidelines for accessible exercise equipment. Methods. This study reviews and evaluated the usability of four existing upper-body exercise equipment for individuals with paraplegia with spinal cord injuries. To assess usability, task performance scores and time were measured, and a survey was conducted on safety and satisfaction. Based on these results, areas for improvement were identified. Through literature review, usability results, and opinions from various stakeholders, eight requirements for universal accessibility were proposed. Results. It is necessary to consider how wheelchair users access the exercise equipment. The access method to the exercise area (facility regulations, auxiliary equipment to be provided, etc.) and placement of exercise equipment should also be considered. Information such as explanations of the exercise equipment and how to use it should be located within the wheelchair user’s field of vision. Considering the participation rate in sports for people with disabilities in Korea, it is necessary to explain the exact exercise equipment and exercise method. It is also necessary to consider how wheelchair users transfer from the wheelchair to the seat of the exercise equipment. Parts that require manipulation of each exercise equipment must be within the wheelchair user’s range of motion. Various supports or assistive devices that provide body support according to each piece of equipment are needed. In addition to the wheelchair’s own brake, it is necessary to provide a fixing device so that the wheelchair does not move during the exercise. Conclusion. For people with spinal cord injuries, the arm ergometer, aerobic exercise equipment, showed higher scores in performance, stability, and satisfaction compared to other exercise equipment. Among the strength exercise equipment, shoulder press had an effect on performance, seated lat pull-down had an effect on stability, and seated chest press had an effect on satisfaction. Therefore, when selecting exercise equipment, it is necessary to recommend aerobic and strength exercise equipment according to the preferences of people with spinal cord injuries. When developing strength exercise equipment, it is necessary to consider usability evaluation factors for individuals with spinal cord injury.